Cristalização e resolução da estrutura tridimensional da lectina de Canavalia maritima (Conm) complexada com o primer da interleucina - 1 beta - Vieira, Derek Barroso Holanda Asp (2014)
Legume lectins are historically recognized as carbohydrate-binding proteins, and this property is roughly linked to the majority of their biological activities, such as pro and antiinflamatory processes, apoptosis and mitogenic mechanisms. However, several studies have demonstrated the capability of these proteins to bind diverse other compounds, such as phytohormones and hydrophobic molecules, although the biological relevance of these interactions remains elusive. Many biological reactions involve proteins interactions with nucleic acids and the protein interaction with DNA plays a key role in the cellular regulation and all vital functions. In the present work, it is reported the crystal structure of ConM, a lectin isolated from Canavalia maritima seeds, in complex with Interleukine 1β primer. A cubic crystal, belonging to the F23 space group, was obtained by the diffusion vapor method and submitted to X-ray diffraction. In the structure, an electron density map corresponding to four nucleotides from the interleukin-1β primer was found in the interface of ConM non-canonical dimer. The nucleotides stabilization involves H-bonds and electrostatic forces with the amino acids His127, Ser110, Lys114, Ser190, Asp192, Thr194, His51 and Ser190. Based on these crystallographic results and in a molecular docking simulation, it is hypothesized that the lectin may function as a transcription factor, which could help us to understand some of their biological activities.